Recovering memory by visualizing our archaeological heritage - Carcedo de Mufarech, Paloma (2018)
The current territory of Lima has an impressive pre-Columbian heritage, works that bear witness to thousands of years of constant transformation of a barren land into a true oasis in the desert belt of the Peruvian coast. However, archaeological monuments in Lima have been historically excluded from the memory of the city, and have not been part of the “limeñidad” in the minds of its people. So it is that the huacas are not considered a part of civic education, nor taken into account in the territorial development policies of Lima, but, considered dangerous and abandoned spaces. The present article reflects on this problem and the actions taken for the management of archaeological heritage by the Management of Culture of the Metropolitan Municipality of Lima from 2011 to 2014, a period in which the Millennial Lima, City of Culture program was developed, which led, not only to the recovery of prehispanic buildings, but, also, to the implementation of an educational project and activities which involved the community with its huacas.